2009
DOI: 10.1080/15374410903401138
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Child and Adolescent Psychopathy Construct in Hong Kong, China

Abstract: This cross-sectional study examined the nature of child and adolescent psychopathy using the Antisocial Process Screening Device (APSD) in 3,675 schoolchildren (ages 11-16) in Hong Kong, China. A confirmatory factor analysis observed a good fit for the three-factor model (callous-unemotional, impulsivity, narcissism) of APSD, with boys scoring higher than girls on narcissism and callous-unemotional traits. Modest construct validity was found with regard to expected relationships with internalizing and external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 32 publications
3
31
1
3
Order By: Relevance
“…The correlations between the conduct disorder diagnosis and the APSD-SR (total score and factors) were low to moderate, and weaker than the ones reported by Frick et al (2000a), which while higher than what we observed were none the less similar to the ones obtained by other authors (e.g., Fung, Gao, & Raine, 2010). Note.…”
Section: Discussioncontrasting
confidence: 63%
“…The correlations between the conduct disorder diagnosis and the APSD-SR (total score and factors) were low to moderate, and weaker than the ones reported by Frick et al (2000a), which while higher than what we observed were none the less similar to the ones obtained by other authors (e.g., Fung, Gao, & Raine, 2010). Note.…”
Section: Discussioncontrasting
confidence: 63%
“…It is nevertheless possible that the callous-unemotional measure differs from the peer victimization and schizotypy measures in terms of social desirability. Data on reliability and validity of the callous-unemotional scale in this sample are provided in Fung, Gao, and Raine (2010). tailed).…”
Section: Peer Victimizationmentioning
confidence: 99%
“…Estas correlações ficaram aquém das correlações mais elevadas obtidas por Frick, Barry e Bodin (2000), mas foram semelhantes às obtidas por outros autores (e.g., Fung, Gao, & Raine, 2010). A validade de critério retrospectiva do APSD total com as variáveis Idade do primeiro crime cometido e Idade do primeiro problema com a lei revelou a existência de correlações negativas moderadas baixas e estatisticamente significativas.…”
Section: Discussionunclassified
“…Tem havido alguns desacordos quanto à sua estrutura factorial. Enquanto alguns autores authors (e.g., Frick, O'Brien, Wootton, & McBurnett, 1994;Pardini, Lochman, & Frick, 2003) defendem uma estrutura bi-dimensional constituída por traços calosos/não-emocionais (CU) e por problemas de impulsividade/comportamento (I-CP), estudos efectuados com amostras maiores (e.g., Dadds, Fraser, Frost, & Hawes, 2005;Fung, Gao, & Raine, 2010) demonstram que o APSD também pode ser conceptualizado como uma estrutura tri-dimensional composta por traços calosos/não-emocionais (CU), impulsividade (Imp) e narcisismo (Nar). Outros autores (e.g., Fite, Greening, Stoppelbein, & Fabiano, 2009) encontraram evidências que apoiam tanto uma estrutura bi-dimensional como uma estrutura tri-dimensional.…”
unclassified